Prediction of noise pollution from construction sites at the planning stage using simple prediction charts - Haron, Zaiton (2012)
Prediction of noise pollution from construction site plays an important role in planning and construction management. However, engineers may have difficulty in making predictions at the planning stage because the acoustic characteristics and location of the source are not precisely known, and many assumptions have to be made. This study focuses on the development of chart predictions based on stochastic modelling, so that the data available at the planning stage can be used to produce a set of noise levels along with standard deviations. The study compares the noise predictions using the chart with the results of measurement, and simulation. Two simple charts in the form of deviations from the mean noise level versus the ratio r/w, and standard deviation versus the ratio r/w, were established based on analysis using stochastic models developed by considering systematic changes in the site parameters. The charts were applied to predict construction noise in a physical case of substructure work. The noise levels predicted using the design charts are slightly higher, by 3 dB(A) and 1 dB(A), than the results obtained using measurement and simulation, respectively. Based on these results, the charts can be used to manually approximate construction noise at the planning stage with reasonable accuracy. The advantages of charts are that the level of noise at various locations of the receiver can be determined manually and quickly using various sound power levels of equipment that may actually be employed in the construction process.